An environment-friendly engine selection methodology for aerial vehicles - Sohret, Yasin; Kincay, Olcay; Karakoc, T. Hikmet (TAYLOR & FRANCIS INC, 2018)
Emitted exhaust gases from aircraft are an issue of concern from an environmental perspective. Many research studies have been conducted aiming to reduce aircraft emissions in the hope of preventing any further increase in climate change and global warming. Within this scope, the present study intends to present a methodology for an optimum gas turbine engine selection with regard to emitted exhaust gases. The methodology focuses on five different turbofan engines which constitute the power unit of a commonly used passenger aircraft. At the end of the study, it is considered to be impossible to achieve a minimum exhaust emission for each gas. For this reason, it is considered to be better to optimize the engine with the aim of reducing nitrogen oxide emissions or other exhaust emissions.
Keywords: Aircraft; emissions; environment; fuel consumption; gas turbine engine; AIRCRAFT EMISSIONS; CIVIL-AVIATION; NOX; IMPACT; PARAMETERS; OPERATIONS; OZONE; MODEL; CO; HC; Thermodynamics; Science & Technology - Other Topics; Energy & Fuels